2023
DOI: 10.1002/jmri.28645
|View full text |Cite
|
Sign up to set email alerts
|

IOP Injection, A Novel Superparamagnetic Iron Oxide Particle MRI Contrast Agent for the Detection of Hepatocellular Carcinoma: A Phase II Clinical Trial

Abstract: BackgroundMRI is crucial in diagnosing hepatocellular carcinoma (HCC). Superparamagnetic iron oxide particles (SPIO) are liver‐specific contrast agents which enhance lesions in T2‐weighted images. Iron oxide nano‐particle m‐PEG‐silane (IOP) Injection, a newly developed SPIO, showed promising imaging effects and good safety profile in preclinical studies and in phase I clinical trial.PurposeTo evaluate the safety and clinical validity of IOP Injection as MRI contrast agent in diagnosing HCC.Study typeProspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Because IOPs are coated with PEG rather than high molecular weight iron dextran products, these new nanoparticles are expected to have a lower risk of immune complex anaphylaxis. Indeed, early phase clinical trials have demonstrated an excellent safety profile of this new agent in-human patients 10 . However, further studies in larger patient populations are needed before conclusions can be drawn regarding the rate of immunologic or nonimmunologic reactions to this new nanoprobe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because IOPs are coated with PEG rather than high molecular weight iron dextran products, these new nanoparticles are expected to have a lower risk of immune complex anaphylaxis. Indeed, early phase clinical trials have demonstrated an excellent safety profile of this new agent in-human patients 10 . However, further studies in larger patient populations are needed before conclusions can be drawn regarding the rate of immunologic or nonimmunologic reactions to this new nanoprobe.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, early phase clinical trials have demonstrated an excellent safety profile of this new agent in-human patients. 10 However, further studies in larger patient populations are needed before conclusions can be drawn regarding the rate of immunologic or nonimmunologic reactions to this new nanoprobe.…”
Section: Iop In Human Osteosarcomasmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,7 In this study, the authors present results from a phase II clinical trial of a new hepatobiliary contrast agent based on iron oxide nanoparticle m-PEG-silane (IOP). 8 Consequently, the aim of this study is to evaluate the effectiveness of the imaging strategy and identify potential side effects of the new contrast agent. The study population was comprised of 52 subjects (seven female) who had previously been diagnosed with HCC via dynamic multiphase CT or MRI.…”
mentioning
confidence: 99%
“…In this study, the authors present results from a phase II clinical trial of a new hepatobiliary contrast agent based on iron oxide nanoparticle m‐PEG‐silane (IOP) 8 . Consequently, the aim of this study is to evaluate the effectiveness of the imaging strategy and identify potential side effects of the new contrast agent.…”
mentioning
confidence: 99%